MORPHOFUNCTIONAL STATE OF PLATELETS IN PATIENTS WITH ACUTE STROKE IN THE THROMBOCYTOPENIA OF UNKNOWN ORIGIN - Tatiana Petrovna Bondar; Evgenia Alexandrovna Kovalenko; Julia Andreevna Zolina; Arthur Iskhakovich Bayramkulov (Современная наука и инновации)
The article contains research materials relating to the issues associated with the development of stroke. The article deals with violations of platelet and plasma hemostasis in acute cerebral circulatory disorders .